2019
DOI: 10.1002/jlb.ma1118-450rr
|View full text |Cite
|
Sign up to set email alerts
|

PD-1 modulating Mycobacterium tuberculosis-specific polarized effector memory T cells response in tuberculosis pleurisy

Abstract: Host‐pathogen interactions in tuberculosis (TB) should be studied at the disease sites because Mycobacterium tuberculosis (M.tb) is predominantly contained in local tissue lesions. T‐cell immune responses are required to mount anti‐mycobacterial immunity. However, T‐cell immune responses modulated by programmed cell death protein 1 (PD‐1) during tuberculosis pleurisy (TBP) remains poorly understood. We selected the pleural fluid mononuclear cells (PFMCs) from TBP and PBMCs from healthy donors (HD), and charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…29 In tuberculous pleural effusions, PD-1-expressing CD4 + and CD8 + T cells had activated phenotype and increased production of Th1 cytokines compared with PD-1 − cells. 30 Our study found a subset of PD-1 high CXCR5 − MAIT cells that were expanded in tuberculous pleural effusions. Although PD-1 high CXCR5 − MAIT cells from tuberculous pleural effusions had reduced IFN-γ level and increased expression of Tim-3 and GITR, they showed activated phenotype and higher glucose uptake and lipid content, suggesting that Mtb infection might promote reprogramming of MAIT cells.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…29 In tuberculous pleural effusions, PD-1-expressing CD4 + and CD8 + T cells had activated phenotype and increased production of Th1 cytokines compared with PD-1 − cells. 30 Our study found a subset of PD-1 high CXCR5 − MAIT cells that were expanded in tuberculous pleural effusions. Although PD-1 high CXCR5 − MAIT cells from tuberculous pleural effusions had reduced IFN-γ level and increased expression of Tim-3 and GITR, they showed activated phenotype and higher glucose uptake and lipid content, suggesting that Mtb infection might promote reprogramming of MAIT cells.…”
Section: Discussionmentioning
confidence: 54%
“…Treatment of patients with cancer by anti‐PD‐1 blockage led to increased risk of TB in humans . In tuberculous pleural effusions, PD‐1‐expressing CD4 + and CD8 + T cells had activated phenotype and increased production of Th1 cytokines compared with PD‐1 − cells . Our study found a subset of PD‐1 high CXCR5 − MAIT cells that were expanded in tuberculous pleural effusions.…”
Section: Discussionmentioning
confidence: 97%
“…This regulation affects other immune cells such as T cells and dendritic cells that also express CD200R ( 150 ). Similarly, the binding of PDL-1 to its receptor PD-1 dampens AM secretion of inflammatory cytokines and negatively regulates T cell effector functions ( 151 , 152 ), whereas binding of CD47 to SIRP1α expressing macrophages downregulate phagocytosis ( 153 , 154 ). Thus, there is a breadth of evidence demonstrating the importance of lung ECs in regulating local immune responses, by interacting/communicating with immune cells, including AMs.…”
Section: Alveolar and Airway Ec Smentioning
confidence: 99%
“…Sustained high expression of PD‐1 has been associated with T cell dysfunction in chronic viral infections and tumors [39]. In human TB, high PD‐1 expression has been observed in T cells from peripheral blood and pleural effusion of patients with TB pleurisy [40] and in circulating CD4 + T cells from S‐TB patients with a positive AFB sputum smear [24]. In our study, we observed a marked increase in the percentage of CD4 + and CD8 + PD‐1 + cells in MDR‐TB compared to S‐TB patients, despite 92% of MDR‐TB and all S‐TB patients having a positive sputum smear at the time of the study.…”
Section: Discussionmentioning
confidence: 99%